Auditory Brainstem Response (ABR) waveform analysis program - Burke, Kali; Burke, Matthew; Lauer, Amanda (MethodsX, 2023)
Auditory brainstem responses (ABR) are a high-throughput assessment of auditory function. Many studies determine changes to the threshold at frequencies that span the normal hearing range of their test subjects, but fewer studies evaluate changes in waveform morphology. The goal of developing this program was to make a user-friendly semi-automatic peak-detection algorithm to encourage widespread analysis of the amplitudes and latencies of the ABR, which may yield informative details about the integrity of the auditory system with development, aging, genetic manipulations, or damaging conditions. This method incorporates automated peak detection with manual override and inter-rater validation to calculate the amplitude and latency for waves 1-5, as well as interpeak latencies and amplitude ratios between waves. The output includes raw data and calculations in a format compatible with graphical and statistical software. The method yields a high-throughput peak-detection algorithm with manual override and inter-rater capabilities to streamline ABR waveform analysis. Data output includes amplitudes, latencies, amplitude ratios, and interpeak latencies for generation of input-output curves. While complete automation of peak detection with this tool is dependent on good signal-to-noise ratios, relevant amplitude and latency calculations are fully automated, and manual spot-checking is simplified to significantly reduce the time to analyze waveforms. [Display omitted]